2012
DOI: 10.1038/srep00539
|View full text |Cite
|
Sign up to set email alerts
|

Altered Death Receptor Signaling Promotes Epithelial-to-Mesenchymal Transition and Acquired Chemoresistance

Abstract: Altered death receptor signaling and resistance to subsequent apoptosis is an important clinical resistance mechanism. Here, we investigated the role of death receptor resistance in breast cancer progression. Resistance of the estrogen receptor alpha (ER)-positive, chemosensitive MCF7 breast cancer cell line to tumor necrosis factor (TNF) was associated with loss of ER expression and a multi-drug resistant phenotype. Changes in three major pathways were involved in this transition to a multidrug resistance phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 61 publications
1
37
0
Order By: Relevance
“…This shift to a more mesenchymal phenotype fits with the current literature suggesting that drug treatment can effect cellular behaviour and plasticity, with EMT linked to chemoresistance in a number of cell lines and tumour types, including breast cancer [22,44-46]. …”
Section: Discussionsupporting
confidence: 85%
“…This shift to a more mesenchymal phenotype fits with the current literature suggesting that drug treatment can effect cellular behaviour and plasticity, with EMT linked to chemoresistance in a number of cell lines and tumour types, including breast cancer [22,44-46]. …”
Section: Discussionsupporting
confidence: 85%
“…Recent studies have shown that an ETS1-mediated transcription of members of the MMP family is responsible for remodelling of the extracellular matrix in both angiogenesis and invasion [48]. Resistance to TNF-α promotes tumourigenesis [49, 50], and elevated miR-221 may have a role in mediating these effects via its suppression of ETS1 [51]. Thus, chronic upregulation of miR-221 in obesity may potentially increase cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate mechanisms by which cancer cells progress to a resistant phenotype, we employed a previously established in vitro model of acquired resistance (27,35,37,39,83), the cell line MCF-7TN-R, which is resistant to both death receptors and chemotherapeutic drugs that depend on p38 MAPK and NF-κB signaling (27,37,55,84). Further, we investigated whether progression to apoptotic resistance also associated with increased hormone-independent tumor formation and p38 signaling.…”
Section: Discussionmentioning
confidence: 99%